Multi-Criteria Decision Making with TOPSIS to Ranking Brazilian Championship Players - Silva, Igor Magno; Contreras, Rodrigo Colnago; Guido, Rodrigo Capobianco (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
The discussion of who is the best player reaches many football groups often being used more subjective standards than objectives to justify their choices, it happens even in professional football teams. Even in a world with increased access to data, there are still teams that base their choices on outdated methods. Therefore, this study was designed to develop a ranking of the Brazilian national championship players using the TOPSIS method, which uses benefit and cost criteria to find the suboptimal option. For this analysis data was collected from the website Football Stats and History, in the end a comparison between the Cartola FC rating and the TOPSIS rank was made.